A fast and simple approach to optimize the unit operation high pressure homogenization - a case study for a soluble therapeutic protein in E. coli. Issue 1 (2nd January 2019) - Pekarsky, Alexander; Spadiut, Oliver; Rajamanickam, Vignesh; Wurm, David J.
Abstract: Escherichia coli is one of the most commonly used host organisms for the production of recombinant biopharmaceuticals. E. coli is usually characterized by fast growth on cheap media and high productivity, but one drawback is its intracellular product formation. Product recovery from E. coli bioprocesses requires tedious downstream processing (DSP). A typical E. coli DSP for an intracellular product starts with a cell disruption step to access the product. Different methods exist, but a scalable process is usually achieved by high pressure homogenization (HPH). The protocols for HPH are often applied universally without adapting them to the recombinant product, even though HPH can affect product quantity and quality. Based on our previous study on cell disruption efficiency, we aimed at screening operational conditions to maximize not only product quantity, but also product quality of a soluble therapeutic protein expressed in E. coli . We screened for critical process parameters (CPPs) using a multivariate approach (design of experiments; DoE) during HPH to maximize product titer and achieve sufficient product quality, based on predefined critical quality attributes (CQAs). In this case study, we were able to gain valuable knowledge on the efficiency of HPH on E. coli cell disruption, product release and its impact on CQAs. Our results show that HPH is a key unit operation that has to be optimized for each product.